Assessment of the BAPFAS Program: A Structured Educational Intervention to Enhance Burn Prevention and First Aid Knowledge Among Schoolchildren - Gorka, Rahul; Shalli, Shalli; Mani, Abhinav; Mohi, Parvez (Indian Journal of Plastic Surgery, 2025)
Burn injuries are a major public health concern, particularly in low- and middle-income countries (LMICs). Children are especially vulnerable due to their limited hazard awareness and inability to respond effectively to burn emergenciesTo assess the effectiveness of the Burns Awareness, Prevention, and First Aid for Schoolchildren (BAPFAS) program in improving knowledge of burn prevention and first aid among school-aged children.A pre-test/post-test interventional study was conducted in 12 schools in Jammu District, involving 1,200 students in grades 8 to 12. The BAPFAS program included structured training using presentations, videos, and demonstrations. Knowledge was assessed at baseline, immediately after training, and at 3-month follow-up using a standardized 10-question questionnaire. Paired t-tests were used to compare pre-test, immediate post-test, and follow-up scores, with t-values, degrees of freedom, and 95% confidence intervals reported for transparency.Immediate post-test scores showed significant improvement over baseline (t = 18.72, p < 0.001, 95% CI [2.45, 2.87]). At 3-month follow-up, scores showed a slight decline but remained significantly higher than baseline (t = 9.34, p < 0.001, 95% CI [1.12, 1.56]). Improvement was consistent across age groups, genders, and urban/rural settings.The BAPFAS program effectively enhanced students' knowledge of burn prevention and first aid, with retention over 3 months. School-based, culturally tailored interventions can be a valuable public health tool to reduce burn-related risks in LMICs.
Keywords: burns awareness; health education; first aid; school children